MENGANALISIS BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP EFEKTIFITAS KINERJA KARYAWAN PADA BENGKEL (JMC) CIKARANG - Nurhalimah Nurhalimah; Dedi Mulyadi; Sungkono Sungkono (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to evaluate how workload and work environment conditions affect employee performance employees at the JMC Cikarang workshop. This research uses a descriptive qualitative qualitative descriptive approach with a case study. Data was collected through in-depth interviews interviews, direct observation, and documentation analysis. Research findings findings show that heavy workload and unsupportive work environment negatively impact employee performance. have a negative impact on employee performance. Conversely, a balanced workload balanced workload and a conducive work environment encourage increased effectiveness of employee performance.